The Glyphosate Assemblage: Herbicides, Uneven Development, and Chemical Geographies of Ubiquity. (Desarrollo, Estado y Espacio, 2025)
The ubiquity of chemicals demands new ways of thinking about human-nature assemblages. This article proposes a dialogue between agrarian political economy, critical value chain research, and chemical geographies, through a case study of the world's most widely used agrochemical: glyphosate. In the 1980s, glyphosate triumphed as a benign biocide that promised both safety and effectiveness. This construct enabled a capitalist agricultural assemblage characterized by chemical omnipresence, first as a chemical replacement for mechanized farming and, since the 1990s, as the chemical input for genetically modified seed packages. The ubiquity that characterizes the glyphosate assemblage is also a geography of uneven development encompassing shifting business, political, and trade networks. A central, though largely overlooked, aspect of this assemblage since 2000 is the unchecked expansion of second- and third-tier generic pesticide producers, particularly in China, for whom glyphosate is part of a series of actions to renew and update their development strategy. Currently, glyphosate formulation faces unprecedented challenges due to weed resistance and health controversies. Whether and how this assemblage stabilizes again will depend on the complex environmental and developmental challenges of chemical agriculture and the widespread use of chemicals, highlighting the need for a transdisciplinary dialogue that can navigate these domains.
Keywords: assemblages; generic herbicides; South-South production networks; weed resistence; health